Assessment of Secondary School Students’ Transversal Skills in Optimal and Highest-Level Mathematics - Kaļķe, Baiba; Āboltiņa, Līga; Lāma, Gatis (Journal of Education Culture and Society, 2025)
Aim. The aim of this study is to assess secondary school students’ transversal skills in mathematics at the optimal and highest level to determine whether education reforms have been implemented successfully. Methods. In total 512 students from grades 11 and 12 participated in the research. Data was gathered by survey. Students transversal skill assessments from optimal and highest level was compared. The data was analysed with descriptive statistics to summarise and describe collected data (Vetter, 2016). Correlation between each transversal skill was made and Mann–Whitney U tests were conducted to determine whether there is a statistically significant difference between the self-assessments of students learning at the optimal and highest levels. Results. The analysis shows that students have adequate transversal skills. However, students self-directed learning skills and civic skills are evaluated lower compared to other transversal skills. Students who learn mathematics at the highest level have assessed their transversal skills higher compared to students who learn mathematics at optimal level. Conclusions. Even though results indicate that students have well developed critical thinking and problem-solving skills, digital skills and collaboration skills, there are some gaps in students’ transversal skills such as self-directed learning and civic participation. Transversal skills more connected to mathematical content or learning methods that promote subject learning are better developed, while other transversal skills that were not included in the previous curriculum should be promoted. This indicates that the recently implemented education reform has not yet been fully implemented into practice.